Organizational capabilities as antecedents of entrepreneurship: A basis for business practice and policy making - Dias, Á.; Pereira, L.; Lopes da Costa, R. (Journal of African Business, 2023)
Entrepreneurship plays an important role on economic development. However, its antecedents are still an under-explored topic. As such, this research seeks to identify the factors that influence entrepreneurship by the relationship between the theoretical fields of entrepreneurship and the Resource Based View. To test the hypothesis, a quantitative study was conducted using survey data from a sample of 118 Angolan entrepreneurs. The results from partial least squares (PLS) allow identifying marketing capabilities; access to financial resources, and innovation capabilities as determinants of entrepreneurship. No significant relation was observed in the link between market experience and customer orientation on entrepreneurship. The implications for business practice and policy making are discussed in the conclusions.